Evaluation of the functional properties of IR64 rice flour - Ronas, Katrina Bautista
IR64 rice flour was evaluated for its functional properties to assess its usefulness in food systems. Proximate analysis was done to characterize the flour in terms of its chemical constituents. IR64 rice flour had 84% moisture, 2.3% total sugars, and 7.2% protein, all of which are low compared to the reference all-purpose flour. Its bulk density was 0.70 g/ml, with water- and fat- absorbing capacities a 217.5% and 205% respectively. Viscosity was determined using spindle number 1 at 50 rpm at 50°C to be 22.5 mPa-s. It is less viscous than all-purpose flour. IR64 rice flour formed a wet mass with water but not the viscoelastic dough. Solubility took place within the pH range 8-14 at 27°C. Gelation occurred at 6%, 8%, 10%, 12%, and 14% concentrations. These evaluations proved the lower functionality of the rice flour relative to all-purpose flour. IR64 rice flour's level of acceptability in chiffon cake was determined. Substitution levels were at 0% (control), 25%, and 50%. Results of consumer acceptance tests showed no significant differences among samples for acceptability of cell size, sweetness, overall flavor and moistness. The use of 50% IR64 rice flour was found significantly more acceptable among samples for overall acceptability, overall appearance and color. The use of 25% IR64 rice flour was found significantly more acceptable for mouthfeel.